2012
DOI: 10.1021/la300856h
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Novel W/O Gel-Emulsions and Their Application in the Preparation of Low-Density Materials

Abstract: A series of novel and stable water in oil (W/O) gel-emulsions was created by utilizing a new cholesteryl derivative, a low-molecular mass gelator (LMMGs), as a stabilizer. In the emulsions, n-heptane, n-octane, n-nonane, n-decane, tertiary butyl methacrylate (t-BMA), methyl methacrylate (MMA), or styrene can be used as a continuous phase, water as a dispersed phase, and the stabilizer in the continuous phase is only 2% (w/v). Importantly, the gel-emulsions could be prepared by simple agitation of the mixtures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 37 publications
0
55
0
1
Order By: Relevance
“…Fourier transform infrared spectra were recorded with a Perkin Elmer Spectrum 100 ATR instrument. For each spectrum, 16 scans were conducted over a spectral range of 4000 to 600 cm ), 63 and showed that the tested gel systems were shear thinning. The rheological measurements were carried out after stabilizing the gels for 60 min in the sample holder at room temperature (25 o C).…”
Section: Methodsmentioning
confidence: 99%
“…Fourier transform infrared spectra were recorded with a Perkin Elmer Spectrum 100 ATR instrument. For each spectrum, 16 scans were conducted over a spectral range of 4000 to 600 cm ), 63 and showed that the tested gel systems were shear thinning. The rheological measurements were carried out after stabilizing the gels for 60 min in the sample holder at room temperature (25 o C).…”
Section: Methodsmentioning
confidence: 99%
“…Calixarene has been studies as a component of gelators. [37][38][39][40][41][42][43][44] Our group have reported two gel works based on calix [4]arene and for the rst time constructed a novel gelator with calix [4]arene fragment and two cholesterol. The rst work of our group based on calix [4]arene was that novel gelator was synthesized and used it prepared smart shearthixotropy gel in the mixture solvent of decane and acetonitrile.…”
Section: -18mentioning
confidence: 99%
“…Physical gels based on self-assembly structure of molecule because of potential application in drug/protein delivery, 1,2 oil spill recovery, [3][4][5] have become one of active frontiers of novel materials in recent years. Researcher struggled to prepare novel physical gel by bonding some functional groups and introducing extraordinary metal ions in gelator molecular or solvent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, mixing speed (Gurevitch and Silverstein, 2010;Sturzenegger et al, 2012), particle concentration (Arditty et al, 2003;Binks and Whitby, 2004;Sturzenegger et al, 2012), particle wettability (Akartuna et al, 2008b;Bachinger and Kickelbick, 2010;Chuanuwatanakul et al, 2011;Haase et al, 2011), particle aspect ratio (Vandebril et al, 2010), particle roughness (San-Miguel and Behrens, 2012), and particle size (Binks and Lumsdon, 2001) have all been studied. Such wet emulsions can be shaped, extruded into forms or coated into sheets because of their measurable yield stress Chen et al, 2012). Once dried, the resulting highly porous green ceramics can be sintered, creating a ceramic foam with open cell microstructure and compressive strengths up to 13 MPa and porosities above 70 vol% (Akartuna et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%